2013
DOI: 10.1111/jcpe.12043
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐cardiolipin from periodontitis patients induces MCP‐1 production by human umbilical vein endothelial cells

Abstract: Aim Periodontal diseases are associated with a variety of systemic diseases, including cardiovascular disease and stroke, and patients with periodontitis demonstrate elevated levels of anticardiolipin antibodies. We sought to determine if anticardiolipin antibodies from periodontitis patients induced monocyte chemotactic protein-1 production by human vascular endothelial cells. Materials and Methods IgG was purified from sera from 53 subjects, including chronic and aggressive periodontitis patients and perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…The previous data indicate that IgG antiCl in sera from patients with CP is biologically active 10 . Isolated IgG from these sera were shown to activate human endothelial cells, stimulating production of MCP‐1 at levels that directly varied with the antiCl titer 10 .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The previous data indicate that IgG antiCl in sera from patients with CP is biologically active 10 . Isolated IgG from these sera were shown to activate human endothelial cells, stimulating production of MCP‐1 at levels that directly varied with the antiCl titer 10 .…”
Section: Discussionmentioning
confidence: 98%
“…14 The previous data indicate that IgG antiCl in sera from patients with CP is biologically active. 10 Isolated IgG from these sera were shown to activate human endothelial cells, stimulating production of MCP-1 at levels that directly varied with the antiCl titer. 10 In addition, removal of antiCl from these immunoglobulin preparations reduced production of MCP-1 from endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MCP‐1 may induce osteoclast differentiation and osteoclastogenesis and relate to bone resorption 46,47 . A recent study published by Schenkein et al 48 also concluded that anti‐CL antibodies may activate endothelial cells to produce MCP‐1, which may result in the association between periodontitis and other systemic conditions. The present study is in line with the previous findings.…”
Section: Discussionmentioning
confidence: 99%